Meagre Argyrosomus regius (Osteichthyes) as host of a gonad-infecting species of Philometra (Nematoda: Philometridae) off the Atlantic coast of Portugal - Moravec, Frantisek; Prista, Nuno; Costa, Maria José (Diseases of aquatic organisms, 2007)
Subgravid females (up to 439 mm long) of the nematode Philometra sp. were found in meagre Argyrosomus regius (Asso, 1801) (Sciaenidae: Perciformes) off the southern Atlantic coast of Portugal in 2006. The general morphology of these nematodes somewhat resembles that of Philometra lateolabracis (Yamaguti, 1935), but the gravid females of the species from A. regius are apparently much longer. This is the first documented record of a gonad-infecting species of Philometra in marine fishes off the Atlantic coast of Europe. The possible importance of the gonad-parasitizing Philometra spp. as pathogens of marine fishes is stressed.
Keywords: Portugal; Microscopy, Electron, Scanning; Nematode Infections; mikroskopie elektronová rastrovací; Atlantic Ocean; nematodózy; Nematoda; Gonads; gonády; Portugalsko; ženské pohlaví; zvířata; Atlantský oceán; nemoci ryb; hlístice; Fish Diseases; Perciformes; Female; Animals